Analisis Camel Pada Bank Syariah dan Dampaknya Terhadap Risiko Kredit - Rakhmat, Adrianna Syariefur; Fahamsyah, Mohammad Hatta; Nurastuti, Preatmi; Ainulyaqin, Muhammad Hamdan (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze the influence of ROA, NPF, NPM, BOPO and FDR on CAR. The sample used in this research used 60 data. The analytical tools used were Classic assumption test, multiple linear regression, t test, F test and determinant coefficient. The research results show that partially the variable Return on Assets (ROA) has a positive and significant effect on the Capital Adequation Ratio (CAR) and the Financing to Deposit Ratio (FDR) has a positive and insignificant effect on the Capital Adequation Ratio (CAR). Meanwhile, Non-Performing Financial (NPF), Net Profit Margin (NPM) and Operating Costs/Operating Income (BOPO) have a negative and significant effect on the Capital Adequation Ratio (CAR). Simultaneously, the variables Return on Assets (ROA), Non-Performing Financing (NPF), Net Profit Margin (NPM), Operational Costs/Operational Income (BOPO), and Financing to Deposit Ratio (FDR) have a significant positive effect on the Capital Adequation Ratio (CAR ). The determinant coefficient r square value of 0.571 means that the variables Return on Assets (ROA), Non-Performing Financing (NPF), Net Profit Margin (NPM), Operational Costs/Operational Income (BOPO), and Financing to Deposit Ratio (FDR) have an impact on The Capital Adequation Ratio (CAR) is 57.1% and there are still other variables remaining at 42.9%